2018
DOI: 10.2478/aopf-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing fish meal with sunflower meal on growth performance, body composition, hematological and biochemical indices of common carp (Cyprinus carpio) fingerlings

Abstract: The aim of the present study was to evaluate the effects of replacing fish meal with sunflower meal had on common carp, Cyprinus carpio L. fingerlings. A total of 455 fish with an average weight of 3.03 ± 0.36 g were distributed in 15 fiberglass tanks and fed five isonitrogenous and isoenergetic diets with replacement levels of 0 (control), 25, 50, 75, and 100% of fish meal with sunflower meal for 10 weeks. Based on the results, the highest and lowest final weights were observed at 25 and 100%, respectively, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
2
13
2
1
Order By: Relevance
“…The results of this study showed that even when differences in amino acid composition were considered, inclusion of 20% sunflower meal in the feed as a replacement for soybean meal did not impair growth performance. These results are in agreement with other studies using Tilapia rendalli, Salvelinus alpinus, Cyprinus carpio in which 20% sunflower meal inclusion did not affect fish performance (Olvera-Novoa et al, 2002;Smith et al, 2017;Rahmdel et al, 2018). On the other hand, fish fed 10% sunflower meal resulted in lower weight gain.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study showed that even when differences in amino acid composition were considered, inclusion of 20% sunflower meal in the feed as a replacement for soybean meal did not impair growth performance. These results are in agreement with other studies using Tilapia rendalli, Salvelinus alpinus, Cyprinus carpio in which 20% sunflower meal inclusion did not affect fish performance (Olvera-Novoa et al, 2002;Smith et al, 2017;Rahmdel et al, 2018). On the other hand, fish fed 10% sunflower meal resulted in lower weight gain.…”
Section: Discussionsupporting
confidence: 92%
“…The limited use of sunflower meal is due to its high fiber content and presence of anti-nutritional factors, although these are minimized during the oil extraction processing (Bergamim et al, 2013;González-Pérez & Vereijken, 2007). Reduction in growth and worsening of feed conversion were evidenced in studies with inclusion levels higher than 20% due to proteolytic enzyme suppression caused by antinutritional factors present in sunflower meal (Lin et al, 2010;Lovatto et al, 2014;Rahmdel et al, 2018) The inclusion of sunflower meal resulted in increased crude fiber levels. In spite of this increase, fish fed these diets showed no alterations in intestinal histology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study for hematological indices were similar to the values detected by others [ 60 , 61 , 62 , 69 ]. Moreover, the hematological parameters assessed in the current experiment were within the physiological ranges for C. gariepinus that were supported by Kumar et al [ 70 ] and Rahmdel, Noveirian, Falahatkar, and Lashkan [ 25 ], who stated that there were no significant variances in hemoglobin, hematocrit, MCV, MCH, and MCHC values in common carp when replacing FM with kernel meal and sunflower meal, respectively. These results suggested that replacing FM with plant protein sources had no harmful consequence on blood parameters, since plant components decrease hematocrit level, which is considered a hazard for the wellbeing of farmed fish [ 71 ].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it could be decreasing the cost without affecting growth performance [ 24 ]. Additionally, Rahmdel et al [ 25 ] stated that sunflower meal could replace up to 75% of fishmeal without any negative effect on growth performance, body composition, and haemato-biochemical indices for common carp fingerlings. These results were supported by Nogales Merida, Jover Cerda, Martínez-Llorens, and Tomás Vidal [ 22 ], who detected that there was no significant effect of replacing fishmeal with different levels of sunflower meal for sharp snout sea bream, Diplodus puntazzo (Walbaum).…”
Section: Introductionmentioning
confidence: 99%